In “Vitro” Lps-Stimulated Sertoli Cells Pre-Loaded With Microparticles: Intracellular Activation Pathways - Arato, Iva; Milardi, Domenico; Giovagnoli, Stefano; Grande, Giuseppe; Bellucci, Catia; Lilli, Cinzia; Bartoli, Sara; Corneli, Sara; Mazzone, Piera; Calvitti, Mario; Baroni, Tiziano; Calafiore, Riccardo; et al. (Frontiers in Endocrinology, 2021)
Sertoli cells (SC) are immune privileged cells with the capacity of modulating the immune response by expressing several immune-regulatory factors. SC have the capacity to respond to external stimuli through innate phagocytic and antibacterial activities. This evidence evoked a potential role of SC as drug carriers and therapeutic agents. Such stimuli drive SC towards a still unknown evolution, the clinical relevance of which as yet remains undisclosed. This study sought to investigate the effects of external stimuli in the form of polymeric microparticles (MP) and bacteria derived endotoxins, such as lipopolysaccharides (LPS), in order to identify the pathways potentially involved in cell phenotype modifications. Compared to single stimulation, when combined, MP and LPS provoked a significant increase in the gene expression of IDO, PD-L1, FAS-L, TLR-3, TLR-4, MHC-II, ICAM-1, TFGβ1, BDF123, BDF129, BDF3 and pEP2C. Western Blotting analysis demonstrated up-regulation of the ERK 1-2 and NF-kB p65phosphorylation ratios. Our study, showing the exponential increase of these mediators upon combined MP and LPS stimulation, suggests a “switch” of SC function from typical cells of the blood-testicular barrier to nonprofessional tolerogenic antigen-presenting cells. Further studies should target the clinical and technological implications of such stimuli-induced SC transformation.